ANALISIS KOMPARATIF EFISIENSI BEBAN PAJAK PENGHASILAN SEBELUM DAN SESUDAH IMPLEMENTASI UNDANG-UNDANG NO 7 TAHUN 2021 TENTANG HARMONISASI PERATURAN PERPAJAKAN PADA PT TELKOM INDONESIA TBK PERIODE 2020-2024 - Aisah, Siti; Komarudin, Mochamad Fachru (Journal of Economics, Accounting, Tax, and Management (JECATAMA), 2026)
This study aims to analyze the impact of the implementation of the Law on Harmonization of Tax Regulations (UU HPP) on the efficiency of income tax burden at PT Telkom Indonesia Tbk. Secondary data used in this study uses financial statement data from 2020 to 2024. By calculating the Effective Tax Rate (ETR) ratio from the comparison of total tax burden and profit before tax, the results of the study show a downward trend in the tax burden in the post-UU HPP period (2023–2024) compared to the previous period (2020–2021). This finding indicates that the company's management has successfully adapted to the applicable tax regulations to achieve more optimal fiscal efficiency without neglecting tax compliance.